Kincir Bertingkat pada Pembangkit Listrik Mikrohidro - Janu Prasetyo; Sunardi Sunardi (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2019)
Electricity is one of the basic needs of the community. The ability of PLN to provide electricity to the Indonesian people is still an obstacle and a challenge. On the other hand Indonesia has so much potential for water that has not been utilized optimally, which is around 75,000 MW and which is currently utilized only at 10.1% or 7,572 MW. Micro hydro power (MHP) with each 5 MW MHP in 2014. This study aims to utilize the remaining water flow from the existing mill for the installation of the second wheel to obtain maximum power. Experiments were carried out using equipment such as embedded iron fast pipes, waterwheel 1 and 2, pulleys, and generators. Installation on the end of the pipe against pin 1 uses the over-flow method to obtain optimal power. The average rotation speed of the generator for mill 1 is around 1500rpm and for the mill 2 around 1000rpm. The final result of this study, for generator 1 on wheel 1 can run smoothly and produce the appropriate output voltage of 220V, for generator 2 the generator 2 the output generator cannot be optimized because the generator component we use requires a minimum of 1500rpm to run it.